Significance of angiotensin 1–7 coupling with MAS1 receptor and other GPCRs to the renin‐angiotensin system: IUPHAR Review 22. (9th March 2017) - Karnik, Sadashiva S; Singh, Khuraijam Dhanachandra; Tirupula, Kalyan; Unal, Hamiyet
Abstract : Angiotensins are a group of hormonal peptides and include angiotensin II and angiotensin 1–7 produced by the renin angiotensin system. The biology, pharmacology and biochemistry of the receptors for angiotensins were extensively reviewed recently. In the review, the receptor nomenclature committee was not emphatic on designating MAS1 as the angiotensin 1–7 receptor on the basis of lack of classical G protein signalling and desensitization in response to angiotensin 1–7, as well as a lack of consensus on confirmatory ligand pharmacological analyses. A review of recent publications (2013–2016) on the rapidly progressing research on angiotensin 1–7 revealed that MAS1 and two additional receptors can function as 'angiotensin 1–7 receptors', and this deserves further consideration. In this review we have summarized the information on angiotensin 1–7 receptors and their crosstalk with classical angiotensin II receptors in the context of the functions of the renin angiotensin system. It was concluded that the receptors for angiotensin II and angiotensin 1–7 make up a sophisticated cross‐regulated signalling network that modulates the endogenous protective and pathogenic facets of the renin angiotensin system.